Literatur Review : Analisis Strategi Pemasaran Digital Dalam Ruang Lingkup Umkm - Kevin Adrigo Siahaan; Jonrian Simamora; muhammad idris (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
The development of digital technology has driven a significant transformation in marketing strategies, especially for Micro, Small and Medium Enterprises (UMKM). This study aims to analyze the effectiveness of the integration of three main approaches in digital marketing, namely influencer marketing, Search Engine Optimization (SEO), and personal content, in improving the competitiveness and sustainability of MSMEs. The method used is a literature review with a descriptive approach, which examines ten scientific articles published in 2019-2024. Data sources were collected through online scientific platforms such as Google Scholar and Research Rabbit, then systematically analyzed to identify patterns, strategies, and impacts of digital marketing implementation by MSME players.The study results show that social media, especially TikTok, Instagram, Facebook, and WhatsApp, are the main channels in reaching consumers and building engagement. Collaboration with micro-influencers is proven to increase brand credibility and expand market reach, while the application of SEO drives increased digital traffic and online visibility. Authentic personalized content also plays an important role in creating an emotional connection between MSMEs and consumers. However, challenges such as limited human resources, digital literacy, and content consistency still hinder the optimization of this strategy.Thus, the integration of the three approaches is considered effective in supporting the growth and sustainability of MSMEs in the digital era. Continuous support is needed in the form of training and mentoring so that MSME actors are able to implement digital marketing strategies optimally and with high competitiveness.